Probiotic Potential of Lactic Acid Bacteria Isolated from Broiler Chickens in Côte d’Ivoire - Sika-Kadji , A.E.; Kéhi, T.B.; N’Guessan, F.K.; Koffi-Nevry, R.A. (International Journal of Poultry Science, 2022)
Objective: The objective of this study was to characterize and assess lactic acid bacteria isolated from the gastrointestinal tract of broilers for their use in poultry farming as potential probiotic in Côte d’Ivoire. Materials and Methods: For this purpose, 90 colonies of lactic acid bacteria isolated from the crop and cecum of broilers were subjected to several probiotic tests: Thermoresistance, tolerance to acid pH and bile salts, self-aggregation and co-aggregation, hydrophobicity, antibacterial activity and sensitivity to antibiotics. Results: The results of this study showed that out of the 90 isolates 44 were resistant to pH 3 and 0.3% bile salt. Of the 44 isolates, 15 showed high probiotic potential. These isolates belong to the species Pediococcus acidilactici (4), Lactobacillus pentosus (4), Weissella confusa (2) Enterococcus faecium (2), Pediococcus pentosaceus (2) and Enterococcus faecalis (1). The heat map analysis also showed that the species with the best probiotic potential were, Lactobacillus pentosus JK (51 and 55) and Enterococcus faecium JK 96. Conclusion: The species Lactobacillus pentosus JK (51 and 55) and Enterococcus faecium JK 96 could be used for the production of probiotic feed for poultry farming in Côte d’Ivoire thus reducing the use of antibiotics.